Film consciousness from phenomenology to Deleuze - Shaw, Spencer 1945- (McFarland, 2008)
"Revisits notions of memory, retentional consciousness, narrative expectation, and spatio-temporal perception while also analyzing several major films. Focuses on understanding the film experience through phenomenology; develops the idea of film consciousness as a unique vision of the world and reality. Combines the ideas of philosophers and film theorists from phenomenology with the postmodernist and transitional theorists"--Provided by publisher